Эмульсан – представитель промышленно важных внеклеточных биополимеров - Пирог, Татьяна Павловна; Гринберг, Тамара Александровна; Дерябин, Владимир Викторович; Малашенко, Юрий Романович (My University, 1990)
Обобщены имеющиеся данные по получению нового типа промышленно важных внеклеточных биополимеров — эмульсанов. Рассмотрены вопросы селекции и усовершенствования штамма-продуцента, особенности роста и образования биополимера на средах, содержащих этанол и углеводородные субстраты, физико-химические свойства биополимера и перспективы применения. The data of the production of a novel type of industrially important extracellular biopolymers — emulsan — are reviewed. The problems of selection and improvement of the strain-producent, its growth properties and formation of the biopolymer on ethanol and carbohydrate substrates are considered. The physico-chemical properties of the biopolymer iand the perspectives of its employment in different branches of industry, are also discussed.
Keywords: эмульсан; биополимеры; этанол; emulsan; biopolymers; ethanol; кафедра біотехнології і мікробіології